Aktuelle Diskussionen zum Ausbau kapitalgedeckter Altersvorsorge als Ergänzung des Rentensystems - Marlene Haupt (Wirtschaftsdienst, 2024)
– Germany faces complex challenges in ensuring adequate pensions and the financial sustainability of its pension system amid demographic aging, necessitating comprehensive reforms. The Focus Group on Private Pensions has proposed measures to reform the private Riester pension scheme, advocating, for example, the enhancement of simplicity, transparency and flexibility. Additionally, it has debated the introduction of a state-mandated fund. The German Council of Economic Experts has also proposed a state-mandated fund with automatic enrollment and an opt-out option. However, the proposal faces skepticism and is widely debated. Despite this, the discussion on a state-mandated fund remains relevant, with political party initiatives even considering mandatory funded pensions.
Keywords: H55; J11; J26; 330; Altersvorsorge; Gesetzliche Rentenversicherung; Deutschland; Altersvorsorge; Gesetzliche Rentenversicherung; Deutschland